Impact of Changes in Soil Attributes and Composition following Anthropization Related to Agricultural Practices in the Amazon Region - Paes da Silva, Rosa de Nazaré; de Souza Mateus, Nikolas; dos Santos, Cássio Rafael Costa; Costa, Milton Garcia [UNESP]; de Oliveira Ferreira, Eric Victor; Viégas, Ismael de Jesus Matos (Springer Nature, 2024)
Abstract: In response to the ongoing expansion of agriculture and land use changes in the Amazon region, new studies are necessary to understand the impacts of agricultural practices on Amazonian soils. The objective was to assess the changes induced in soil horizons by different management practices. The research was conducted in the National Forest of Caxiuanã, located in the municipality of Melgaço, Pará State, Brazil. A completely randomized 3 × 4 factorial design was employed, incorporating three types of vegetation (20-year-old secondary forest—SoilFS20, 5-year-old secondary forest—SoilFS5, and coivara—cutting and burning of native vegetation—SoilLTM) and four effective soil depths (0–5 cm, 5–10 cm, 10–20 cm, and 20–30 cm), with nine replicates for each combination. To enhance accuracy of the required assessment of the modifications induced in the physical and chemical attributes of the soil, isotopic composition of δ13C and δ15N was utilized. In areas subjected to clearing (SoilFS5 and SoilLTM), significant concentrations of carbon (C) and nitrogen (N) were observed in the 20–30 cm depth due to soil disturbance, which incorporated the litter into the deeper horizons. However, no significant differences in the C/N ratio were detected among the studied areas at the effective soil depth. Regardless of soil depth, SoilFS20 exhibited lower acidity, δ13C, δ15N, sandy and clay content, as well as iron (Fe) content, while displaying higher levels of SOM, zinc (Zn), calcium (Ca), manganese (Mn), potassium (K), silt, sodium (Na), copper (Cu), and phosphorus (P) content compared to the other sites. The results showed significant variations in the chemical and physical properties of the soil among the study sites, with SoilFS20 standing out in several characteristics. The increase in carbon stock in SoilFS20 indicated positive responses to specific management practices. Analyses of carbon, nitrogen concentrations, and stable isotopes highlighted SoilFS5 as distinctly different from the others. These findings contribute to the understanding of soil dynamics under different management practices, providing valuable insights for sustainable natural resource management in the region.
Keywords: Soil anthropization; Soil chemical attributes; Soil management; Soil organic matter; Stable isotope analysis